Anticoagulant activity of some Artemisia dracunculus leaf extracts - Kemal Durić; Elvira E Kovac Besovic; Haris Niksic; Samija Muratovic; Emin Sofic (Biomolecules & Biomedicine, 2015)
Platelet hyperactivity and platelet interaction with endothelial cells contribute to the development and progression of many cardiovascular diseases such as atherosclerosis and thrombosis. The impact of platelet activity with different pharmacological agents, such as acetylsalicylic acid and coumarin derivatives, has been shown to be effective in the prevention of cardiovascular disease. Artemisia dracunculus, L. Asteraceae (Tarragon) is used for centuries in the daily diet in many Middle Eastern countries, and it is well known for its anticoagulant activity. The present study investigates the presence of coumarins in tarragon leaves and subsequently determines the extract with a major amount of coumarin derivatives. The solvents of different polarities and different pH values were used for the purpose of purifying the primary extract in order to obtain fractions with the highest coumarin content. Those extracts and fractions were investigated for their anticoagulant activity by determining prothrombin time (PT) and the international normalized ratio (INR), expressed in relation to the coagulation time of the healthy person. Purified extracts and fractions obtained from plant residue after essential oil distillation, concentrated in coumarin derivatives, showed the best anticoagulant activity, using samples of human blood. INR maximum value (2.34) and consequently the best anticoagulant activity showed the methanol extract at concentration of 5%.  The INR value of normal plasma in testing this extract was 1.05.